Clinical efficacy of PD-1 inhibitor combined with radiotherapy in a multi-drug resistant patient with liver metastasis from gastric cancer - Xu, Judi; Liu, Hedai; Ni, Guoying; Huang, Yan; Huang, Ying; Liang, Hongxiang; Ni, Yufeng; Huang, Qian; Yang, Zhiyong (Frontiers in Surgery, 2023)
A 54-year-old male was diagnosed with extensive liver metastasis and small nodule metastasis in the lungs from gastric adenocarcinoma [Her-2 (−)]. The patient achieved significant partial response (PR) after chemotherapy combined with anti-angiogenesis therapy but developed progressive disease (PD) after 5 months. Then, the chemotherapeutic and anti-angiogenic drugs were replaced. Meanwhile, the delivery route of some chemotherapeutic drugs was changed, and some chemotherapeutic drugs were given via transcatheter arterial chemoembolization (TACE) to achieve PR, and PD developed after 3 months of remission maintenance. During chemotherapy combined with anti-angiogenesis, the application of programmed cell death-1 (PD-1) inhibitor achieved PR again and maintained for 5 months before disease progression. The progression of the lesions in the left lobe of the liver and the hepatic hilar lymph nodes was significant. Hence, chemotherapy was terminated and gamma stereotactic body radiation therapy (SBRT) was performed on left lobe lesions and hilar lymph nodes. The lesions both inside and outside the radiation field regressed significantly, reaching PR and abscopal effects. The immune-related adverse events (irAEs) occurred, including erythema and black and luster hair. The abscopal effects of lesion reduction in the radiation field and the enhancement of the immune function stimulated by radiation are a highlight of the combination of radiation and immunotherapy. In the end, the patient died of gastrointestinal failure, with overall survival of 18 months.